h-45=-9

Simple and best practice solution for h-45=-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for h-45=-9 equation:


Simplifying
h + -45 = -9

Reorder the terms:
-45 + h = -9

Solving
-45 + h = -9

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '45' to each side of the equation.
-45 + 45 + h = -9 + 45

Combine like terms: -45 + 45 = 0
0 + h = -9 + 45
h = -9 + 45

Combine like terms: -9 + 45 = 36
h = 36

Simplifying
h = 36

See similar equations:

| 5*x^2+7*y^2+100=0 | | 16+13x=20-x | | 6x+110=17x-11 | | X^2-16x+20=-43 | | -145-3x=-12x+80 | | 6x+2x-7x+4=10 | | 2.3x-1=35 | | 6(x+4)+16=-2x | | 8x+5=9x-14 | | 12x+4-(x+3)= | | 14+20x=17-x | | -3(-n-4)-2=-n+34 | | 3(3x-7)=5(2x-3)method | | 2(4-2)+4=20 | | 2=70+1x | | -4x-1=2 | | 5+x=13+2x-2x | | 4x-3y-10=1 | | 68=2x | | 4x-4-7x=29 | | -189=-15x-6x | | (x-2)=105 | | x/0.5=0 | | 3/4a6 | | 1-9h^2=12h | | 5/6x5/6 | | 7(u-5)-4=-4(-4u+6)-3u | | 16+.49x=16 | | 13x+3=3x+103 | | -37-5x=-10x+48 | | 2(x-4)=-4+22 | | 7n-1+8=-7 |

Equations solver categories